Advanced Materials as Adsorbents in Microextractions for the Determination of Contaminants: A Mini Review - Rozaini, Muhammad Nur' Hafiz; Saad, Bahruddin; Ramachandran, Muggundha Raoov; Abdul Kadir, Evizal (Faculty of Engineering, Universitas Indonesia, 2019)
The widespread presence of contaminants in water demands reliable and practical analytical methods to monitor them. However, before their determination, a sample pretreatment step is necessary. This has conventionally been performed using liquid-liquid extraction (LLE) or solid-phase extraction (SPE). Advances in material sciences have since been capitalized on, with new adsorbents used in conjunction with new sample pretreatment techniques based on microextractions. In this mini-review, we showcase some of our previously reported work that demonstrates how advanced materials such as graphene, molecularly imprinted polymers (MIPs), and polymeric cyclodextrins can be used as adsorbents for the determination of contaminants such as bisphenol A, steroids, sulfonamide antibiotics, and antimicrobial agents. These adsorbents formed an important component in the micro-solid phase extraction that was used for the pretreatment of the sample. A brief introduction to the adsorbents studied and evolution of extractions is provided. The distinctive features of the analytical methods used in the real sample analysis of the stated contaminants are highlighted. © 2019 Faculty of Engineering, Universitas Indonesia.